Evaluation Of Anti-inflammatory Mediated Anti-hemorrhoidal Activity of Lawsonia inermis on Croton Oil Induced Hemorrhoidal Rats - Nallajerla, Sai K.; Ganta, Suhasin (Anti-Inflammatory & Anti-Allergy Agents in Medicinal Chemistry, 2022)
Background: Hemorrhoids are a common recto-anal disorder commonly known as piles or tissue clumps in the rectum. In normal individuals, they were known as anal cushions. In the anus, they are composed of rectal blood vessels, muscles, and elastic fibres. When bulged, it can cause bleeding, constipation, itching, severe pain, and bleeding in the anus. Inflammation of the anal cushion remains major pathogenesis for the development of hemorrhoids. Inflammatory mediators like neutrophils, TNF-α, and IL-6 seem to play a major role in the development of disease. Objective: This study aims to carry out the ethanolic leaf extract of Lawsonia inermis (L. inermis) and evaluate its anti-hemorrhoidal activity both in vitro and in vivo. Furthermore, Molecular Docking was performed on the crystal structure of COX-2 with the selective compound 23d-(R) (PDB ID: 3NTG) protein. Methods: The current study is to estimate an anti-inflammatory mediated anti-hemorrhoidal activity of ethanolic leaf extract of L. inermis at different doses of 200 mg/kg/ir and 400 mg/kg/ir in croton oil-induced hemorrhoidal rats. Pilex ointment is taken as a reference standard in the present study. Evan's blue extravasation technique were applied in the study to quantify the proinflammatory protein. Results: From the study results, a dose-dependent effect was found for ethanolic leaf extract of Lawsonia inermis at 200 mg/kg and 400 mg/kg causing a significant reduction of serum Proinflammatory mediators TNF-α, IL-6, and plasma neutrophils in croton oil-induced hemorrhoidal rats. Conclusion: Studies represented that the plant extract can significantly inhibit protein denaturation of egg albumin in in vitro and found to reduce croton oil induced inflammatory mediators in hemorhhoidal rats.
Keywords: hemorrhoids